Upaya Pemerintah Indonesia Dalam Penyebaran Budaya Indonesia Di Jepang (2008-2013) - Hemas Septiani; Ratnawati Ratnawati (Jurnal Paradigma, 2014)
Through diplomacy and spread the culture of Indonesia introduced Indonesian culture in Japan. The deployment of Indonesian culture has begun intensively since 2008 and the results starts with a clearly visible increase in visitor Indonesian festival in Japan, an increase of Japanese tourists to Indonesia, and the improvement of Japanese investors in Indonesia